A Separator with a Novel Thermal Crosslinking Structure Based on Electrospun PI/A‐POSS for Lithium‐Ion Battery with High Safety and Outstanding Electrochemical Performance. Issue 24 (17th November 2021) - Song, Xiaoyan; Wang, Zhen; Zhao, Fangzheng; Sun, Yizhe; Cheng, Bowen; Xing, Jinfeng
Abstract: In this study, a polyimide/aminopropyllsobutyl polyhedral oligomeric silsesquioxane (PI/A‐POSS) membrane with a novel 3D thermal crosslinking structure is prepared by electrospinning and subsequent imidization. Compared with the pure PI membrane, PI/A‐POSS composite membranes present better mechanical properties, narrower distribution of pore size, smaller average pore size, and better thermal stability. When A‐POSS content is 3 wt%, the composite membrane (A3) has outstanding electrolyte uptake, excellent ionic conductivity, low interfacial resistance, and the high electrochemical stability of anode. The battery assembled with the A3 separator has an excellent first discharge capacity of 137.8 mAh g −1 and its capacity retention rate is still as high as 76.49% after 100 cycles at 2.0 C. Furthermore, battery assembled with the A3 separator shows excellent rate capacity with a relatively high discharge capacity up to 169.7 mAh g −1 at 0.2 C and a superior capacity recovery rate of 98.06% at 30 °C. Especially, the battery assembled with the A3 separator shows more prominent rate capacity with an excellent first discharge capacity up to 180.5 mAh g −1 at 0.2 C and a superior capacity recovery rate of 95.79% at 60 °C. Abstract : An A3 separator with a novel thermal crosslinking structure can effectively inhibit the growth of lithium dendrites and enhance the migration rate of lithium ions in a working lithium‐ion battery. Therefore, this separator can effectively improve the safety performance, cycle performance, and rate capacity of the lithium‐ion battery.